Saving for a rainy day: Estimating the appropriate size of U.S. state budget stabilization funds - Bo Zhao (Federal Reserve Bank of Boston, 2014)
Rainy day funds (RDFs) are potentially an important countercyclical tool for states to stabilize their budgets and the overall economy during economic downturns. However, U.S. states have often found themselves exhausting their RDFs and having to raise tax rates or reduce expenditure while still experiencing a downturn. Therefore, how much each state should save in its RDF has become an increasingly important policy question. To address this issue, this paper develops target RDF levels for each U.S. state, based on the estimated short-term revenue component associated with business cycles and also on states' preferences for stable tax rates and expenditure. The analysis shows that in the last 25 years at least 21 states have never saved enough in their RDFs relative to their needed RDFs. The paper provides policy recommendations on reforming the RDF caps.
Keywords: E32; E63; H71; H72; 330; rainy day funds; budget stabilization funds; revenue cyclicality